SLAC and SNAC Wrist: The Top Five Things That General Radiologists Need to Know - Eliza Kompoliti; Mikaella Prodromou; Apostolos H. Karantanas (Tomography, 2021)
Wrist osteoarthritis (OA) is a common painful condition that affects the patient’s quality of life by limiting the range of wrist motion and grip strength. Wrist OA often results from scapholunate advanced collapse (SLAC) or scaphoid nonunion advanced collapse (SNAC). Early diagnosis of SLAC and SNAC is crucial because it affects treatment planning. Thus, radiologists should be able to interpret the early imaging findings. This pictorial review discusses the pathophysiology and the clinical symptoms of SLAC and SNAC and presents the imaging findings with emphasis on the proper imaging algorithm. Finally, it focuses on the treatment according to the degenerative status of each of these patterns.